Assessing Delay Factors and Mitigation Measures in Building Maintenance Works - Yasin, Mohd Norazam; Razman, Ruzaimah; Nagapan, Sasitharan; Moayedi, Farzaneh (International Journal of Sustainable Construction Engineering and Technology, 2023)
When it comes to the operation of a construction industry, building maintenance is critical. Any structure must be well-maintained to prevent minor problems from becoming major ones. Delayed building maintenance may result in increased repair costs as well as a reduction in building lifespan. To avoid this problem, research has been conducted to identify the factors that cause building maintenance delays and mitigation measures to resolve building maintenance delays. To achieve the study’s objectives, extensive literature research and a questionnaire survey were conducted. Based on previous literature research, accumulated data was used to create a questionnaire for 250 Malaysian building maintenance delay factors and mitigation measures. A group of professionals and experts, including top management, project managers, engineers, architects, assistant engineers, technicians, human resources and administration, and others, participated in this survey. SPSS statistical software was used to analyse the collected data using the average mean index method and correlation. According to the data, the three highest mean index values from the factors that cause maintenance work delays are an increase in maintenance costs as the building age increases, an incorrect timing for work can incur higher maintenance costs when a critical job item is overlooked, and improper planning and budgeting. For correlation analysis, it was found that the correlations amongst the five groups of delay factors are having strong relationship with Pearson correlation value of 0.5. While for mitigation measures of the delay, it was found that three highest ranks are prefer other organizational structure follows by policy and objective and good communication. The findings can assist construction practitioners in prioritising their maintenance works.